Endoscopic Imaging After Right Main Bronchus Recanalization Through Bronchoscope with Stent Placement (Revista de Medicina Clinica, 2023)
Clinical Snapshot on "Endoscopic Imaging After Recanalization of the Right Main Bronchus through Bronchoscope with Stent Placement" presented in volume 7 issue 1 of 2023 of Revista de Medicina Clínica.
Keywords: bronchoscopy; Endoprosthesis; bronchopulmonary carcinoma